Subcutaneous Low-Molecular Weight Heparin or Oral Anticoagulants for the Prevention of Deep-Vein Thrombosis in Elective Hip and Knee Replacement? - Hamulyák, Karly; Lensing, Anthonie W A; van der Meer, Jan; Smid, Willem M; van Ooy, André; Hoek, Jaap A; for the Fraxiparine Oral Anticoagulant Study Group (Thrombosis and Haemostasis, 1995)
Objective. To compare efficacy, safety, and feasibility of adjusted- dose oral anticoagulants (OAC) versus fixed-dose subcutaneous low molecular weight heparin (LMWH) for the prevention of deep venous thrombosis (DVT) in patients who have undergone elective hip or knee replacement.Design. Multicentre, single blind randomised trial. OAC (acenocoumarol, target International Normalised Ratio, 2.0-3.0) and LMWH (nadroparine, 60 aXa IU/kg once daily) were started preoperatively and continued for 10 days. All outcome measures were adjudicated by an independent committee unaware of treatment allocation.Subjects. 672 consecutive patients scheduled for elective hip or knee replacement surgery. All patients wore bilateral graduated compression stockings.Main outcome measures. The endpoint for the assessment of efficacy was venography confirmed DVT or confirmed symptomatic pulmonary embolism. The endpoint for the assesment of safety was clinically important bleeding during study treatment or within 48 h of the end of treatment.Results. Among the 517 patients with interpretable venograms, 391 had a hip replacement and 126 had a knee implant. DVT was demonstrated in 50 (20%) of 257 patients allocated to OAC and 43 (17%) of 260 patients allocated to nadroparine (p = 0.45), for an absolute difference in DVT incidence of 2.9% in favour of nadroparine (95% Cl, -3.7-9.5). Clinically important bleeding occurred in eight (2.3%) of the 342 oral anticoagulant treated patients and in five (1.5%) of the 330 nadroparine treated patients (p = 0.62), for an absolute difference in favour of nadroparine of 0.8% (95% Cl, -1.3-2.9).Conclusion. Patients who undergo major orthopaedic operations have a high risk of venous thromboembolism. Once daily fixed-dose subcutaneous nadroparine is at least as efficacious and safe as daily adjusted OAC for prophylaxis against DVT after hip or knee implantation but is more simple to administer.